Airborne ultrafine particles in a naturally ventilated metro station: Dominant sources and mixing state determined by particle size distribution and volatility measurements. (August 2018) - Mendes, Luís; Gini, Maria I.; Biskos, George; Colbeck, Ian; Eleftheriadis, Konstantinos
Abstract: Ultrafine particle number concentrations and size distributions were measured on the platform of a metro station in Athens, Greece, and compared with those recorded at an urban background station. The volatility of the sampled particles was measured in parallel, providing further insights on the mixing state and composition of the sampled particles. Particle concentration exhibited a mean value of 1.2 × 10 4 # cm −3 and showed a weak correlation with train passage frequency, but exhibited a strong correlation with urban background particle concentrations. The size distribution appears to be strongly influenced by outdoor conditions, such as the morning traffic rush hour and new particle formation events observed at noon. The aerosol in the metro was externally mixed throughout the day, with particle populations being identified (1) as fully refractory particles being more dominant during the morning traffic rush hours, (2) as core-shell structure particles having a non-volatile core coated with volatile material, and (3) fully volatile particles. The evolution of particle volatility and size throughout the day provide additional support that most nanoparticles in the metro station originate from outdoor urban air. Graphical abstract: Image 1 Highlights: Particle concentrations in the metro were within the range measured in urban air. The outdoor air appears to be the major source of nanoparticles in the metro. Aerosol in the metro was externally mixed, and most particles had a refractory core. Abstract : Ultrafine particles concentration in the metro were within the range of those in urban air, and are originated mainly from outdoors, even though the metro is naturally ventilated.